PEMANFATAN DAUN TEBU KERING (DADHOK) DENGAN PENAMBAHANBLOTONG DAN AKTIVATOR EM4 UNTUK PEMBUATAN KOMPOSDI KECAMATAN KREMBUNG KABUPATEN SIDOARJO TAHUN 2015 - Fathwa Rakhmawati Kirana; Imam Thohari (GEMA LINGKUNGAN KESEHATAN, 2015)
Dry sugarcane leaves (dadhok) are garbages of sugar cane harvest that have not been managedproperly. One of the alternatives to reduce pollution generated is to use it as compost. This studyaims to determine content of dry sugarcane leaves as compost with the addition of blotong andEM4 activator.This research uses experimental design with Pre-Post Test Only Design. There were fourexperiments conducted within the study: 1st experiment was dry sugarcane leaves (control), 2experiment was dry sugarcane leaves + EM4 activator, 3blotong, 4thrd experiment was dry sugar cane leaves +  experiment was dry sugar cane leaves + EM4 activator + blotong. Data was collectionby measurement and laboratory testing. Data was then analyzed descriptively by referring to theRegulation of the Minister of Agriculture numbers 70 / Permentan / SR.140 / 10/2011 and SNI 197030-2004.Resultshows that of the four experiments conducted, C / N ratio of compost that met the requirement was the 2nd, 3rd, and 4th experiment but only the 3ripe compost requirement (color, texture, smell). Compost of 2ndrd and the 4th experiments fulfilled  experiment was not perfectly ripefor  EM4 only reduce the value of C / N ratio but it cannot degrade the material. On experiment 1,C / N ratio and compost ripeness did not meet the requirement. Macronutrients of all experimentsdid not meet the requirement. This was because the raw material had low macronutrients.Findings conclude that only the 3rd and the 4th experiments meet the requirement of PermentanRegulation number 70 / Permentan / SR.140 / 10/2011 and SNI 19-7030-200. Experiment 1 and 2were not qualified. Findings suggest sugar mills to distribute the abundant waste of blotong tofarmers that it can be used with dry sugarcane leaves as compost. For community who possessugar cane plantations, sugarcane leaves can be used as compost that they can use it to increasetheir income.